The Study of Anemia Prevalence and Some Related Factors among Pregnant Women in Health Centers of Mazanderan in 2015 - Ghahraman Mahmoudi; Bahman Nick Pour; Maryam Khazaee-Pool; Fereshteh Majlessi (Tehran University of Medical Sciences, 2017)
Background and Aim: Iron deficiency anemia is one of the most common nutritional problems of women in reproductive age, which has a major impact on fetal growth, low birthweight and premature delivery. This study aimed to assess the prevalence of anemia and related factors in pregnant women having referred to health centers of Mazandaran province. Materials and Methods: In this descriptive-analytical study, 866 pregnant women were selected through stratified cluster sampling method from 19 cities, affiliated to Mazandaran University of Medical Sciences. Data was collected by using the registration form and information obtained through maternal family documents and a questionnaire. SPSS software version 18 was used and the data were analysed by descriptive and analytical statistics such as mean comparison test, chi-square and logistic regression.  Results: The prevalence of anemia in Mazandaran was 13.4% and it was higher among pregnant women in urban areas than those in rural areas. Logistic regression showed that mother's age, number of pregnancies, prenatal care, unwanted pregnancy, consumption of red meat, using iron tablets, tea drinking, and mother's education level had a significant effect on anemia. Conclusion: Since iron deficiency anemia is a preventable problem and pregnant women are among the vulnerable groups, considering care programs before and during pregnancy, having appropriate dietary patterns, consumption of iron supplements, and having a program to prevent unwanted pregnancies may lead to reducing the risk of catching a disease.